Antagonistic Actions of FPA and IBM2 Regulate Transcript Processing from Genes Containing Heterochromatin. Issue 1 (27th February 2019) - Deremetz, Aurélie; Le Roux, Clémentine; Idir, Yassir; Brousse, Cécile; Agorio, Astrid; Gy, Isabelle; Parker, Jane E.; Bouché, Nicolas
Abstract : Intronic heterochromatic marks, associated with alternative polyadenylation sites, are decoded by RNA-binding proteins like FPA and IBM2, to tune the expression of key regulator genes such as IBM1 or RPP7. Abstract: Repressive epigenetic marks, such as DNA and histone methylation, are sometimes located within introns. In Arabidopsis ( Arabidopsis thaliana ), INCREASE IN BONSAI METHYLATION2 (IBM2), an RNA-binding protein containing a bromo-adjacent homology domain, is required to process functional transcript isoforms of genes carrying intronic heterochromatin. In a genetic screen for suppressors of the ibm2 mutation, we identified FPA, an RNA-binding protein that promotes use of proximal polyadenylation sites in genes targeted by IBM2, including IBM1 encoding an essential H3K9 histone demethylase and the disease resistance gene RECOGNITION OF PERONOSPORA PARASITICA7 . Both IBM2 and FPA are involved in the processing of their common mRNA targets: Transcription of IBM2 target genes is restored when FPA is mutated in ibm2 and impaired in transgenic plants overexpressing FPA . By contrast, transposons targeted by IBM2 and localized outside introns are not under this antagonistic control. The DNA methylation patterns of some genes and transposons are modified in fpa plants, including the large intron of IBM1, but these changes are rather limited and reversed when the mutant is complemented, indicating that FPA has a restricted role in mediating silencing. These data reveal a complex regulation by IBM2 and FPA pathways in processing mRNAs of genes bearing heterochromatic marks.